Impact of Chinese one-child policy on sibling structure: experience from rural areas in three provinces. Issue 3 (2nd June 2012) - Hemminki, Elina; Long, Qian; Wu, Zhuochun; Klemetti, Reija
Abstract : Objectives: To study the influence of population policy and boy preference on the sibling structure, that is, in which order and combinations boys and girls are born into families. Design: A population-based survey with a representative sample of new mothers in 2008–2009 in rural China. Setting: Two provinces (Anhui and Shaanxi) where authorisation for a second child was usually given if the first birth was a daughter and one province (Chongqing) where only one child was authorised. Participants: The mothers giving birth in 2008–2009 were identified from family planning and hospital birth registers (including births outside hospitals) (n=5049). Of them, 3673 were interviewed by trained medical university staff members and students using structured questionnaire (response rate 73%). Main outcome measures: Children's distribution by sex and families' distribution by children's birth order and sex composition were calculated and compared with theoretical values based on the assumption that family planning policy is fully followed. Results: The recommended family policy was varyingly followed in the three provinces. In all provinces, there were more second children than allowed. If the policy allowing a second child only after a first-born girl were fully followed, it would result in a sibling structure in which the one-child family is always with a boy and in the two-child family the first one is always a girl. This sibling structure was partly seen in Anhui but weakly in Shaanxi. The policy allowing only one child would result in an equal number of boys and girls, but in Chongqing, there were more boys. In Anhui, unlike the other provinces, there were many more first-born girls than boys, which the authors could not fully explain. Conclusion: Population policy and boy preference influence the actual and relative number of girls and boys and also sibling structure.